2021
DOI: 10.1002/aocs.12555
|View full text |Cite
|
Sign up to set email alerts
|

The composition of edible oils modifies β‐sitosterol/γ‐oryzanol oleogels. Part I: Stripped triglyceride oils

Abstract: The role of the fatty acid (FA) composition of triglycerides (TAGs) on sterol/sterol ester oleogels has been studied. Minor oil components of three vegetable oils with varying degrees of unsaturation (iodine values, IV) were removed. Typical oil quality parameters were determined before and after the treatment, and oleogels were produced using all six oils. Characteristic gel properties such as transition temperatures, mechanical properties and microstructure were tested. The results were compared regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 29 publications
7
26
0
Order By: Relevance
“…The previous study reported that polar compounds in SBO and genetically modified SBO's significantly lowered the firmness of SW‐based oleogels (Hwang et al, 2018). In contrast, stripped canola, sunflower and flaxseed oils provided significantly softer β‐sitosterol/γ‐oryzanol oleogels compared to the original oils (Scharfe et al, 2021). To understand how the polar compounds in HSO affected the properties of the wax‐based oleogels, polar compounds in HSO was stripped off, and the stripped HSO (SHSO) was used to make 5% wax oleogels with four waxes, SW, RBW, CDW, and BW to compare their properties with 5% wax‐HSO oleogels.…”
Section: Resultsmentioning
confidence: 99%
“…The previous study reported that polar compounds in SBO and genetically modified SBO's significantly lowered the firmness of SW‐based oleogels (Hwang et al, 2018). In contrast, stripped canola, sunflower and flaxseed oils provided significantly softer β‐sitosterol/γ‐oryzanol oleogels compared to the original oils (Scharfe et al, 2021). To understand how the polar compounds in HSO affected the properties of the wax‐based oleogels, polar compounds in HSO was stripped off, and the stripped HSO (SHSO) was used to make 5% wax oleogels with four waxes, SW, RBW, CDW, and BW to compare their properties with 5% wax‐HSO oleogels.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constant of the oil phase containing different weight fractions of various emulsifies was measured using a TU Berlin self‐constructed capacitor. Details of the equipment are described elsewhere (Scharfe et al, 2022a). The determinations were performed in triplicate at a temperature of 20°C (±0.5°C) and with a frequency of 1 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were heated from 0 to 120°C at a constant heating rate of 10°C/min. The gel–solution (gel–sol) transition temperatures were identified as the peak melting temperature at which the dissolution of the tubules occurs (i.e., break‐up of hydrogen bonding between sitosterol and oryzanol) (Scharfe et al, 2022a, 2022b). The gel–solution (gel–sol) transition temperatures are presented as relative values (°C/°C) with respect to that of the neat gel sample prepared with decane only, thus without additives or co‐solvents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations